A desert roadbed and its reinforcement method and application
Patent Information
- Application Number
- CN202610788785.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2046-06-03
AI Technical Summary
现有加固方法如砾石换填、土工合成材料加筋、化学固沙剂喷洒及生物矿化技术,虽各有成效,但普遍存在成本高、施工复杂、环境破坏大及加固效果不均或周期长的问题
[0017] The technical solution provided by one or more embodiments of this application involves screening undisturbed aeolian sand along a desert highway, mixing the fine-grained component with chopped geotextile fibers, and then adding the coarse-grained component to form a mixture. This improves the material's density and shear strength through particle size classification and fiber reinforcement, while providing a uniform nucleation substrate for subsequent calcium carbonate precipitation. Subsequently, a bio-inducing agent is mixed with a composite calcium source cementing liquid to prepare a biomineralization solution, which is then sprayed into the mixture for further mixing. This causes calcium carbonate to precipitate on the surface of sand particles and fibers, forming a cemented structure and further enhancing the interparticle bonding and microscopic stability. The mixture is then vibrated and compacted within a preset time to improve density, uniformly distribute the mineralization solution, and establish preliminary bearing capacity. By repeatedly mixing, mineralizing, and vibrating and compacting in layers according to a preset thickness, the desert roadbed is filled. The shoulders and slopes are then sprayed with a mineralization solution and cured, ensuring not only uniform overall reinforcement but also the formation of a gradient cemented structure. This improves tensile, shear, and wind erosion resistance, achieving long-term stability and durability of the roadbed.
Smart Images

Figure CN122344854B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of desertification control technology, and in particular to a desert roadbed and its reinforcement method and application. Background Technology
[0002] With the accelerated development of highway construction in desert areas, aeolian sand, due to its uniform particle size, lack of cohesion, low shear strength, and poor water stability, has become a major challenge for roadbed construction. Existing reinforcement methods, such as gravel replacement, geosynthetic reinforcement, chemical sand-fixing agent spraying, and biomineralization technology, while each with its own effectiveness, generally suffer from high costs, complex construction, significant environmental damage, and uneven reinforcement effects or long cycles. Furthermore, traditional techniques neglect the active role of fine-grained components in biomineralization and the synergistic effect of fiber, fine-grained, and coarse sand interface calcium carbonate cementation, resulting in "point-to-point" stress concentration in the reinforced body, poor overall integrity, insufficient ductility, and inability to withstand large loads.
[0003] Therefore, how to develop a desert highway subgrade reinforcement technology that can utilize local materials, provide rapid reinforcement, and has high load-bearing capacity and is environmentally friendly is an urgent technical problem that needs to be solved. Summary of the Invention
[0004] This application provides a desert roadbed and its reinforcement method and application, which provides the technical effects of desert highway roadbed reinforcement technology that can use local materials, quickly reinforce, and has high load-bearing capacity and environmental friendliness.
[0005] To achieve the above objectives, the main technical solutions adopted in this application include: In a first aspect, embodiments of this application provide a method for reinforcing a desert roadbed, the reinforcement method comprising: The original aeolian sand along the desert highway was screened, and the screened fine particles were mixed with chopped geofibers and screened coarse particles to prepare a mixture. The biomineralization solution obtained by mixing the bio-inducing agent with the composite calcium source cementing solution is sprayed into the mixture and stirred to obtain the mixed material; The mixture is vibrated and compacted within a preset time to form a roadbed reinforcement layer; Repeat the steps of preparing the mixture, preparing the mix, and vibrating and compacting the material layer by layer according to the preset thickness to fill the desert roadbed to be reinforced in layers. After filling to the design elevation, spray the biomineralization solution on the road shoulders and slopes and maintain them to form a reinforced desert roadbed.
[0006] In one embodiment, the fine-grained component accounts for 50-80% of the pore volume of the coarse-grained component, and the mineral components in the fine-grained component include one or more of illite and montmorillonite. The chopped geofiber is selected from one or more of alkali-resistant glass fiber, polypropylene fiber, or polyacryl alcohol fiber. The chopped geofibers are 12-18 mm in length and are added at a rate of 0.3-0.6% of the total mass of the mixture.
[0007] In one embodiment, the biological inducer includes an EICP biological solution or a MICP bacterial solution; The total calcium ion concentration in the composite calcium source cementing solution is 1.5-2.0 mol / L, and the urea concentration is 1.5-2.0 mol / L.
[0008] In one embodiment, the biomineralization solution obtained by mixing the bio-inducing agent with the composite calcium source cementing solution is sprayed into the mixture and stirred to obtain a mixed material, comprising: The biological inducer and the composite calcium source cementing solution are mixed at a volume ratio of 1:1 to obtain a biomineralization solution.
[0009] In one embodiment, the vibration compaction includes: Perform static compaction once using a vibratory roller, followed by 2-3 vibratory compaction passes until the compaction degree reaches over 96%.
[0010] In one embodiment, the preset thickness is 20-30cm.
[0011] In one embodiment, the spraying rate of the biomineralization solution applied to the road shoulder and slope is 1.5-2.0 L / m². 2 The maintenance mentioned refers to covering the geotextile and maintaining moisture for at least 48 hours.
[0012] In one embodiment, the biomineralization solution contains 0.1-0.3% by mass of a water-retaining thickener, wherein the water-retaining thickener is hydroxypropyl methylcellulose or xanthan gum.
[0013] Secondly, embodiments of this application provide a desert roadbed obtained by the above-described desert roadbed reinforcement method, comprising: Coarse-grained components, which come into contact with each other to form a load-bearing skeleton; Fine-grained components fill the pores of the coarse-grained components; Short-cut geofibers are three-dimensionally randomly distributed between the coarse-grained component and the fine-grained component; And calcium carbonate cement; The calcium carbonate cement fills the space between the coarse-grained component, the fine-grained component, and the short-cut geofibers, forming a continuous cement network. The surface of the fine-grained component is covered with a calcium carbonate crystal layer, and a calcium carbonate anchoring layer is formed on the surface of the short-cut geofibers. The calcium carbonate crystal layer and the calcium carbonate anchoring layer are interconnected.
[0014] In one embodiment, the fine-grained component is an active clay mineral, and the surface of the fine-grained component is covered with a calcium carbonate crystal layer composed of calcium carbonate crystals with a particle size of 5-20 μm, wherein the calcium carbonate crystals are uniformly distributed in a thin film with the fine-grained component as the nucleation substrate.
[0015] In one embodiment, the desert roadbed has a compaction degree of ≥96%, a calcium carbonate content of 1-2%, an unconfined compressive strength of ≥2.0MPa, a failure strain of ≥2.3%, and a pore coordination number distribution exhibiting a bimodal characteristic dominated by isolated micropores.
[0016] Thirdly, this application provides an application of desert roadbed, in which the desert roadbed obtained by the above-described desert roadbed reinforcement method or the above-described desert roadbed is applied to highway roadbed filling, shoulder reinforcement, slope protection or wind and sand disaster prevention projects in desert areas.
[0017] The technical solution provided by one or more embodiments of this application involves screening undisturbed aeolian sand along a desert highway, mixing the fine-grained component with chopped geotextile fibers, and then adding the coarse-grained component to form a mixture. This improves the material's density and shear strength through particle size classification and fiber reinforcement, while providing a uniform nucleation substrate for subsequent calcium carbonate precipitation. Subsequently, a bio-inducing agent is mixed with a composite calcium source cementing liquid to prepare a biomineralization solution, which is then sprayed into the mixture for further mixing. This causes calcium carbonate to precipitate on the surface of sand particles and fibers, forming a cemented structure and further enhancing the interparticle bonding and microscopic stability. The mixture is then vibrated and compacted within a preset time to improve density, uniformly distribute the mineralization solution, and establish preliminary bearing capacity. By repeatedly mixing, mineralizing, and vibrating and compacting in layers according to a preset thickness, the desert roadbed is filled. The shoulders and slopes are then sprayed with a mineralization solution and cured, ensuring not only uniform overall reinforcement but also the formation of a gradient cemented structure. This improves tensile, shear, and wind erosion resistance, achieving long-term stability and durability of the roadbed. Attached Figure Description
[0018] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments of this application and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 A flowchart illustrating a desert roadbed reinforcement method provided in this application embodiment; Figure 2 The mechanism diagram provided in the embodiments of this application; Figure 3 This is a schematic diagram illustrating the effect of different mix proportions provided in Example 1 on the strength of a desert roadbed. Figure 4 The microstructure SEM image provided in Example 2; Figure 5(a) is a schematic diagram showing the effect of different compaction loads on the dry density of the specimen provided in Example 3; Figure 5(b) is a schematic diagram showing the effect of different compaction loads on the unconfined compressive strength (UCS) of the specimen provided in Example 3; Figure 5(c) is a schematic diagram showing the effect of different compaction loads on the compaction degree of the specimen provided in Example 3; Figure 6 The stress-strain curves provided in Example 3 under different compaction loads and fine particle content; Figure 7 The image shows the X-CT three-dimensional reconstruction and pore network model analysis results provided in Example 3; Figure 8(a) is a schematic diagram showing the effect of different mixing ratios provided in Example 4 on ultrasonic speed and calcium carbonate content; Figure 8(b) is a schematic diagram showing the effect of different mixing ratios on resistivity provided in Example 4 of this invention. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0020] Currently, with the continuous advancement of infrastructure construction, especially in highway construction in desert areas, the demand for soil reinforcement technology is becoming increasingly urgent. Aeolian sand, widely distributed in desert regions, poses a significant challenge to desert highway subgrade construction due to its uniform particle size, lack of cohesion, low shear strength, and poor water stability. Traditional reinforcement methods, such as gravel replacement, geosynthetic reinforcement, chemical sand-fixing agent spraying, and biomineralization technology, while achieving some success in certain aspects, still face a series of problems including high energy consumption, complex construction, high costs, and environmental damage.
[0021] First, while gravel-soil replacement can improve roadbed performance by replacing aeolian sand, its high transportation costs and environmental damage pose significant challenges to its practical application. In particular, the need to transport gravel over long distances from outside the desert not only increases costs but also disrupts the ecosystem along the route. Second, while geosynthetic reinforcement can improve the overall integrity of the roadbed to some extent, its improvement in soil strength is very limited, and it faces problems such as material aging and strength degradation. Chemical sand-fixing agent spraying can rapidly reinforce aeolian sand, but its high cost, severe environmental pollution, and poor durability limit its application. Traditional biomineralization technology, despite its environmental friendliness, suffers from weak and uneven reinforcement effects and long reinforcement cycles in practical applications, greatly restricting its economic benefits.
[0022] More seriously, existing reinforcement technologies have not fully recognized the crucial role of naturally occurring fine-grained components in aeolian sand during the biomineralization process. These fine particles not only exist as physical fillers but also play a key role in the reinforcement process. Their small particle size allows them to act as active nucleation sites, regulating the crystallization behavior of calcium carbonate—a role often overlooked in traditional reinforcement methods. Furthermore, the interfaces between fibers, fine particles, and coarse sand can also form a synergistic cementing network through calcium carbonate crystallization, effectively improving the overall strength and stability of the roadbed.
[0023] In traditional biomineralization reinforcement, calcium carbonate crystals mainly concentrate at the contact points of coarse particles, forming a "point-to-point" stress concentration pattern. This makes the reinforced soil prone to localized failure under load. This pattern results in reinforced soil with poor overall integrity and insufficient ductility, making it difficult to withstand large loads. The key to solving this problem lies in transforming the "point-to-point" stress concentration into a uniform force transmission pattern of "surface stress." By forming a uniform network structure through calcium carbonate crystallization, the soil can better distribute the load, thereby improving its bearing capacity and stability.
[0024] Therefore, how to develop a desert highway subgrade reinforcement technology that can utilize local materials, provide rapid reinforcement, and has high load-bearing capacity and is environmentally friendly is an urgent technical problem that needs to be solved.
[0025] This application provides an embodiment of a desert roadbed reinforcement method. Figure 1 A flowchart of a desert roadbed reinforcement method provided in this application embodiment is shown below. Figure 1 As shown, the process includes the following steps: Step S1: The original aeolian sand along the desert highway is screened, and the screened fine particles are mixed with short-cut geotextile fibers into the screened coarse particles to obtain a mixture.
[0026] Specifically, please refer to Figure 2 The schematic diagram provided in this application illustrates the mechanism of sieving untouched aeolian sand along a desert highway to separate fine-grained components with a particle size less than 0.075 mm and coarse-grained components with a particle size greater than or equal to 0.075 mm. The sieved fine-grained components are pre-mixed with chopped geotextile fibers to form a fiber-fine sand mixture. This step uses a road mixer for turning, controlling the turning depth to 20-25 cm, and the mixing is performed at least twice. This aims to better disperse the fibers using fine sand and prevent them from clumping in subsequent processes. Preferably, the amount of fine-grained component added is strictly controlled to be 50-80% of the pore volume of the coarse-grained component. This ratio not only achieves physical pore filling and increases density, but more importantly, the surface of the fine particles preferentially adsorbs urease or urease-producing bacteria through electrostatic attraction. This makes the fine particles a heterogeneous nucleation substrate for subsequent biomineralization reactions, forming locally high-concentration reaction micro-regions at the microscopic level, guiding the directional growth of calcium carbonate crystals.
[0027] The fiber-fine sand mixture described above is thoroughly mixed with the sieved coarse-grained component to obtain a gradation-optimized and uniformly dispersed fiber mixture. The coarse-grained component forms the skeleton of the subgrade, the fine-grained component fills the pores, and the short-cut geofibers form a reinforcing network in three-dimensional space, acting like micro-reinforcing bars to improve the tensile and shear strength of the mixture.
[0028] Step S3: The biomineralization solution obtained by mixing the bio-inducer with the composite calcium source cementing solution is sprayed into the mixture and stirred to obtain the mixed material.
[0029] Specifically, a bio-inducing agent is mixed with a composite calcium source cementing solution (usually a mixture of urea and calcium chloride) in a specific ratio to activate and prepare a biomineralization solution. Specifically, the bio-inducing agent and the composite calcium source cementing solution are mixed at a 1:1 volume ratio using a static mixer. The biomineralization solution is then uniformly sprayed into the mixture prepared in step S1 and thoroughly mixed to obtain a mixed material. The microbial-induced calcium carbonate precipitation reaction begins immediately upon mixing. Pre-mixing and storage can lead to premature precipitation in the cementing solution within the storage tank, causing pipe blockage and loss of effective components. The process of dual-liquid storage and online mixing using a static mixer ensures the chemical stability of the cementing solution before injection into the soil and achieves uniform molecular-level contact during mixing, guaranteeing efficient and uniform reaction within the soil pores.
[0030] This implementation calculates the single-layer spraying volume based on the pore volume of the current treated soil layer. The spraying volume is controlled between 5% and 15% of the pore volume. The standard for controlling the spraying volume is to keep the soil near its optimum moisture content. This design is crucial, as it must ensure the moisture environment required for microbial metabolism while preventing bleeding and softening after subsequent compaction operations, thus maintaining the stability of the soil structure.
[0031] During the mixing process, microorganisms catalyze the hydrolysis of urea during their metabolism, raising the pH value of the environment and promoting the combination of calcium ions and carbonate ions. This causes solid crystals to precipitate at the contact points of the sand grains, thus firmly binding the loose sand grains together.
[0032] Step S5: Vibrate and compact the mixture within a preset time to form a roadbed reinforcement layer.
[0033] Specifically, the mixture is vibrated and compacted within a preset time period (i.e., the working time when microbial activity is optimal and the cementing reaction has not yet begun on a large scale). Vibration compaction not only improves the density of the material but also allows the biomineralization solution to be distributed more evenly in the pores, laying the foundation for the subsequent formation of a dense, high-strength cemented structure. After compaction, a preliminary roadbed reinforcement layer is formed.
[0034] As mentioned earlier, the fine-grained component acts as a nucleation substrate, inducing heterogeneous nucleation of calcium carbonate on its surface, resulting in a uniform calcium carbonate crystal layer. The coarse-grained component, as the main load-bearing unit, is coated with a calcium carbonate film and forms a continuous interfacial transition with the calcium carbonate crystal layer, enhancing the intergranular bonding force. Short-cut geofibers act as a three-dimensional anchoring network, with their surfaces forming rough calcium carbonate anchoring layers due to biomineralization. These calcium carbonate anchoring layers interweave and overlap with the fine-grained calcium carbonate composite. At the interfaces of the three components (fiber, fine-grained, and coarse-grained), continuous gradient cemented bridges are formed. This structure not only transfers stress but also effectively inhibits the propagation of microcracks, significantly improving the tensile and shear strength of the subgrade.
[0035] Step S7: Repeat the above steps of preparing the mixture, preparing the mix and vibrating compaction layer by layer according to the preset thickness to fill the desert roadbed to be reinforced in layers. After filling to the design elevation, spray the surface of the road shoulder and slope with biomineralization solution and maintain it to form the reinforced desert roadbed.
[0036] Specifically, following the preset thickness (20-30cm), steps S1, S3, and S5 are repeated layer by layer to fill the desert roadbed to be reinforced. Layered construction is crucial to ensuring the overall compaction and uniformity of the roadbed. After filling to the design elevation, the exposed surface layers such as the shoulders and slopes are additionally sprayed with a biomineralization solution. This step is equivalent to forming a high-strength surface crust layer, which can effectively resist wind and water erosion. Finally, curing is carried out to provide suitable temperature and humidity conditions for the continuous mineralization reaction of microorganisms, ensuring the full formation of calcium carbonate precipitation, ultimately forming a reinforced desert roadbed with strong integrity and good durability.
[0037] This embodiment provides a desert roadbed reinforcement method. The original aeolian sand along the desert highway is screened, and the fine-grained component is mixed with chopped geotextile fibers, followed by the addition of coarse-grained components to form a mixture. This mixture improves the material's density and shear strength through particle size classification and fiber reinforcement, while providing a uniform nucleation substrate for subsequent calcium carbonate precipitation. Subsequently, a bio-inducing agent is mixed with a composite calcium source cementing liquid to prepare a biomineralization solution, which is then sprayed onto the mixture for further mixing. This causes calcium carbonate to precipitate on the surface of sand particles and fibers, forming a cemented structure and further enhancing the interparticle bonding and microscopic stability. The mixture is then vibrated and compacted within a preset time to further increase density, uniformly distribute the mineralization solution, and establish initial bearing capacity. By repeatedly mixing, mineralizing, and vibrating and compacting in layers according to a preset thickness, the desert roadbed is filled. The shoulders and slopes are then sprayed with the mineralization solution and cured. This not only ensures uniform overall reinforcement but also forms a gradient cemented structure, improving tensile, shear, and wind erosion resistance, thus achieving long-term stability and durability of the roadbed.
[0038] In one optional embodiment, the amount of fine-grained component added accounts for 50-80% of the pore volume of coarse-grained component, and the mineral components in the fine-grained component include one or more of illite and montmorillonite. The chopped geofibers are selected from one or more of alkali-resistant glass fibers, polypropylene fibers, or polyacryl alcohol fibers; The length of the short-cut geofiber is 12-18mm, and the dosage is 0.3-0.6% of the total mass of the mixture.
[0039] Specifically, illite and montmorillonite are layered silicate clay minerals with significant specific surface area and surface charge activity. In microbial-induced calcium carbonate precipitation reaction systems, the surfaces of these clay mineral particles can enrich urease-producing bacteria and calcium ions through electrostatic adsorption, serving as heterogeneous nucleation sites for calcium carbonate crystal growth. Controlling the admixture content at 50-80% is based on a balance between the filling effect and the risk of expansion. Below 50%, the clay minerals are insufficient to form a continuous nucleation network, resulting in minimal improvement in cementation efficiency; above 80%, due to the strong hydrophilic swelling property of montmorillonite, excessive clay minerals may cause the solidified soil to expand in volume upon contact with water, thereby triggering microcracks in the roadbed structure.
[0040] During the biochemical reaction process of microbial-induced calcium carbonate precipitation, urea hydrolysis generates ammonium and carbonate ions, leading to a significant increase in the pH of the pore fluid (typically pH > 9). The alkali-resistant glass fibers (usually doped with zirconium oxide) or synthetic polymer fibers (polypropylene, polyacrylamide) selected in this embodiment possess excellent resistance to acid and alkali corrosion, ensuring long-term structural integrity and maintaining the reinforcement effect in the high-pH environment of biomineralization. For example, polyacrylamide fibers have good hydrophilicity; compared to hydrophobic polypropylene fibers, their surface is more easily wetted by the bacterial solution, which is beneficial for the deposition and interlocking of calcium carbonate crystals on the fiber surface, thereby enhancing the interfacial bonding strength between the fiber and the soil matrix.
[0041] The fiber length of 12-18 mm is the result of optimization for the particle size distribution of aeolian sand. If the fiber is too short (<12 mm), it cannot form an effective crossing and bridging between soil pores, resulting in weak reinforcement. If the fiber is too long (>18 mm), it is prone to entanglement and clumping during mechanical mixing, leading to uneven dispersion and the formation of weak structural surfaces. A length of 12-18 mm is sufficient to form a stable reinforcement network in three-dimensional space, while ensuring good workability. A mass dosage of 0.3-0.6% corresponds to the critical volumetric dosage of fiber-reinforced soil. Within this range, the fiber is uniformly and discretely distributed in the soil, maximizing the frictional reinforcement and cohesion effects. When the soil is subjected to shear loads and microcracks are generated, the fibers crossing the cracks can transmit tensile stress and limit crack propagation; however, a fiber density exceeding 0.6% not only increases costs, but also may hinder the transport of bacterial solution in the pores, which is detrimental to the uniformity of biocementation. Preferably, the short-cut geofiber is alkali-resistant glass fiber with a fiber length of 15 mm and a dosage controlled at 0.4% of the total mass of the mixture.
[0042] In this embodiment, the fine-grained component accounts for 50-80% of the pore volume of the coarse-grained component. Minerals such as illite and montmorillonite, with their large specific surface area and surface charge activity, can enrich urease-producing bacteria and calcium ions, serving as nucleation sites for calcium carbonate precipitation, thereby accelerating soil solidification and enhancing structural strength. The chopped geotextile fibers are selected from alkali-resistant glass fibers, polypropylene fibers, or polyacrylamide fibers, with a length of 12-18 mm, and are added at 0.3-0.6% of the total mass of the mixture. They remain stable in high pH environments and form a three-dimensional reinforcement network in the soil, effectively limiting crack propagation and improving shear strength. By rationally controlling the type, length, and dosage of the fine-grained component and fibers, not only is the strength and crack resistance of the soil enhanced, but the uniformity and operability of construction are also ensured, achieving a long-term stable effect of soil microbial-induced calcium carbonate precipitation improvement.
[0043] In one optional implementation, the bioinducer includes EICP biological solution or MICP bacterial solution; The total calcium ion concentration in the composite calcium source cementing solution is 1.5-2.0 mol / L, and the urea concentration is 1.5-2.0 mol / L.
[0044] Specifically, the bio-inducing agent is selected from EICP biological solution (urease solution) or MICP bacterial solution (urease-producing microbial solution). The concentration of the EICP biological solution (urease solution) is controlled at 100-150 g / L, and the urease activity is ≥15 mmol / (L·min). Highly active urease can rapidly catalyze the hydrolysis of urea, producing carbonate ions, increasing the local pH, and thus inducing rapid precipitation of calcium carbonate. This activity threshold ensures that the reaction can still proceed at a sufficient rate under the high temperature or arid environment of the desert, forming effective cementitious strength. The MICP bacterial solution (urease-producing microbial solution) is a Sporosarcina pasteurii bacterial solution, with a bacterial concentration OD... 600 The optical density should be controlled between 1.0 and 2.0. This optical density value corresponds to a high density of active bacterial communities. The high concentration of bacteria not only provides an ample source of enzymes, but their cell walls can also serve as nucleation sites for calcium carbonate crystals, further enhancing the cementing effect.
[0045] The core chemical reaction in microbial-induced calcium carbonate precipitation technology follows a 1:1 stoichiometric ratio, meaning that 1 mole of urea hydrolyzes to generate 1 mole of carbonate, which then combines with 1 mole of calcium ions to form 1 mole of calcium carbonate precipitate. Setting both concentrations between 1.5-2.0 mol / L ensures optimal stoichiometric balance of the reaction substrates, avoiding waste or residue caused by an excess of any one component. If the concentration is below 1.5 mol / L, the amount of precipitation per unit volume is insufficient, making it difficult to form a high-strength cemented network in a short time, and requiring more spraying times, increasing construction costs. If the concentration is above 2.0 mol / L, excessively high ionic strength may inhibit the activity of microorganisms or enzymes, and an excessively rapid reaction rate can easily lead to rapid blockage of grouting pipe openings or surface pores in the soil, hindering solution penetration to deeper layers and resulting in uneven reinforcement. The 1.5-2.0 mol / L range ensures high precipitation while maintaining good solution permeability.
[0046] In this embodiment, the bio-inducing agent includes EICP bio-solution or MICP bacterial solution, which, when used in conjunction with a composite calcium source cementing solution, achieves efficient, uniform, and stable soil reinforcement. Specifically, the EICP bio-solution contains highly active urease, which can rapidly catalyze the hydrolysis of urea to generate carbonate ions and increase the local pH value, thereby promoting the rapid precipitation of calcium carbonate. The high-density microorganisms in the MICP bacterial solution not only provide an ample enzyme source, but their cell walls can also serve as nucleation sites for calcium carbonate crystallization, further enhancing the cementing effect. The concentrations of calcium ions and urea in the composite calcium source cementing solution are controlled at 1.5-2.0 mol / L, ensuring a near 1:1 stoichiometric ratio for uniform and sufficient precipitation, while maintaining good solution permeability to avoid pipe blockage and uneven soil reinforcement. Through reasonable selection of bio-inducing agents and control of substrate concentration, rapid formation of high-strength calcium carbonate precipitate can be achieved, improving the shear strength and structural stability of the soil, while ensuring the economy and controllability of construction operations, achieving a long-term reliable soil improvement effect.
[0047] In an optional embodiment, a biomineralization solution obtained by mixing a bio-inducing agent with a composite calcium source cementing solution is sprayed into a mixture and stirred to prepare a mixed material, comprising: The bio-inducing agent and the composite calcium source cementing solution were mixed at a volume ratio of 1:1 to obtain a biomineralization solution.
[0048] Specifically, theoretically, 1 mole of urea needs to react with 1 mole of calcium ions (such as CaCl2) to generate 1 mole of calcium carbonate precipitate. In the aforementioned embodiments of this scheme, the concentrations of urea and total calcium ions in the composite calcium source cementing solution are clearly limited to the range of 1.5-2.0 mol / L. This means that the two solutions are molarly equal. Therefore, using a 1:1 volume ratio for mixing ensures that urea and calcium ions reach perfect stoichiometric equilibrium at the moment of mixing. This precise matching maximizes the utilization rate of the reaction substrate, avoids waste due to an excess of one component, or limited calcium carbonate precipitation due to an insufficient amount of one component, thereby ensuring that the maximum amount of cementing material is generated per unit volume of solution.
[0049] Furthermore, the 1:1 volume ratio simplifies metering and mixing control during construction. On-site, whether using a dual-tank, dual-pump system or a static mixer, equal-volume mixing is the easiest mode to implement and control. Operators only need to ensure the same flow rate for both solutions, significantly reducing equipment complexity and the risk of human error. Simultaneously, equal-volume mixing helps create a stable flow pattern within the mixer, promoting turbulent mixing of the two solutions and enabling rapid, uniform contact at the molecular level. This lays the foundation for a uniform mineralization reaction within the soil pores. Using a non-1:1 ratio not only requires more complex metering equipment but may also lead to uneven mixing, resulting in localized reactions that are too fast or too slow, affecting the uniformity of the final reinforcement.
[0050] In this embodiment, a bio-inducing agent and a composite calcium source binder are mixed at a 1:1 volume ratio to obtain a biomineralization solution. This solution is then sprayed into the mixture and stirred to obtain the final mixture. This mixing ratio ensures that urea and calcium ions reach stoichiometric equilibrium in molar concentration, maximizing the utilization rate of the reaction substrate and avoiding waste or precipitation limitations due to excessive or insufficient components. Simultaneously, equal-volume mixing helps create a stable flow pattern within the mixer, promoting turbulent mixing of the solutions and enabling rapid and uniform contact of the two solutions at the molecular level, ensuring the uniformity and efficiency of the mineralization reaction. This process simplifies construction operations, eliminating the need for complex metering equipment. Operators only need to ensure that the flow rates of the two solutions are the same, reducing equipment complexity and the risk of human error, and improving the controllability and stability of the construction. Ultimately, through this precise matching and uniform reaction, the resulting mixture exhibits higher density and strength, significantly improving the shear strength and long-term stability of the soil.
[0051] In one optional implementation, vibration compaction includes: Perform static compaction once using a vibratory roller, followed by 2-3 vibratory compaction passes until the compaction degree reaches over 96%.
[0052] Specifically, vibratory compaction is not a simple mechanical operation, but a physical densification process tailored to the rheological properties and solidification mechanism of this novel composite material: biomineralization solution + fiber + aeolian sand. After spraying and mixing the biomineralization solution, the mixture is loose and has a high moisture content. The main function of the first pass of static compaction is to use the weight of the roller to initially level and seal the surface of the loosely laid mixture. In desert areas with strong winds, the dense surface layer formed by static compaction can effectively reduce the rapid evaporation of water in the underlying biomineralization solution, ensuring a suitable reaction environment for microorganisms or enzymes. At the same time, this hard shell can prevent the splashing or segregation of fine particles containing bacterial solution or cementing solution during subsequent high-frequency vibration, ensuring that the cementing material remains inside the roadbed. Static compaction creates initial interlocking between sand particles, providing a stable medium for the transmission of subsequent vibration waves and preventing the vibratory roller from vibrating idly or slipping on the loose sand surface.
[0053] Next, aeolian sand is an aerosol soil, lacking cohesion between particles. The high-frequency, low-amplitude vibration waves generated by the vibratory roller can instantly reduce the friction and capillary tension between sand particles, causing the soil to liquefy. In this state, sand particles move towards the position of lowest potential energy under gravity, allowing fine particles and fibers to fill the pores between coarse particles. For the incorporated short-cut geotextile fibers, static pressure is insufficient to fully extend them. The shear force of vibration helps the fibers change from a coiled state to an extended state in the soil and align themselves along the stress direction, thus more effectively forming a three-dimensional reinforced network. The pore water pressure fluctuations generated by vibration help the biomineralized solution further diffuse and distribute evenly within the pore network, preventing local enrichment or depletion of cementitious fluid.
[0054] This embodiment utilizes a statically compressed hard shell to prevent fine particles and cementitious liquid from splashing or segregating during subsequent high-frequency vibration, ensuring the cementitious material is uniformly retained within the subgrade. Vibration reduces friction and capillary tension between sand particles, liquefying the sand mass. At this point, fine particles and fibers fill the pores between coarse particles, further increasing compaction. Simultaneously, the shear force of vibration causes short-cut geofibers to extend from their coiled state and align oriented along the stress direction, forming a three-dimensional reinforced network, improving the soil's shear strength and stability. Finally, the pore water pressure fluctuations generated by vibration facilitate the uniform diffusion of the biomineralization solution within the pore network, preventing local enrichment or depletion, thus ensuring uniform cementitious liquid distribution and further enhancing the overall strength and durability of the material. Through this series of operations, an ideal compaction degree of over 96% is achieved, ensuring the material's density and stability, and meeting engineering requirements.
[0055] In one optional embodiment, the spraying rate of the biomineralization solution for the road shoulder and slope is 1.5-2.0 L / m². 2 The curing process involves covering the geotextile and maintaining its moisture for at least 48 hours.
[0056] Specifically, if the spraying rate is less than 1.5 L / m 2 If the cementing solution per unit area is insufficient to fill the pores between surface sand grains, the resulting calcium carbonate crystals will be distributed in a dotted rather than continuous network pattern, failing to form an effective wind-erosion resistant crust, and may still peel off under strong winds; if the spraying rate exceeds 2.0 L / m², further damage will occur. 2 Excessive solution can lead to oversaturation of the surface sand, causing sagging or flowing, which not only wastes material but may also cause shrinkage cracks due to excessive local cementation. 1.5-2.0 L / m 2 The spraying volume ensures that the solution penetrates to a depth of about 1-2 cm into the surface sand. This depth ensures the formation of a hard protective layer on the surface and also provides a good anchoring connection between the protective layer and the underlying roadbed, preventing the protective shell from peeling off completely under thermal expansion and contraction or external forces.
[0057] In this embodiment, when spraying the biomineralization solution onto the road shoulder and slope, the spraying rate should be controlled at 1.5-2.0 L / m². 2 During the curing process, the soil must be covered with geotextile for at least 48 hours to maintain moisture. If the spraying rate is too low, the cementitious solution cannot fully fill the pores between the surface sand grains, resulting in a dotted distribution of calcium carbonate crystals, which is difficult to form an effective wind erosion-resistant layer and is easily peeled off under strong winds. If the spraying rate is too high, the solution becomes oversaturated, leading to sagging or flowing, wasting material and potentially causing shrinkage cracks. The spraying rate should be controlled at 1.5-2.0 L / m². 2 The spraying volume ensures that the biomineralization solution penetrates to a depth of approximately 1-2 cm, forming a hard protective layer on the surface and providing good anchorage to the underlying subgrade, preventing peeling of the protective layer due to thermal expansion and contraction or external forces. After 24 hours of moisturizing curing, it effectively promotes the biomineralization reaction, enhances the strength and durability of the protective layer, and ensures the long-term stability of the road shoulder and slope.
[0058] In one optional embodiment, the biomineralization solution contains 0.1-0.3% by weight of a water-retaining thickener, wherein the water-retaining thickener is hydroxypropyl methylcellulose or xanthan gum.
[0059] Specifically, the most prominent characteristic of desert environments is intense evaporation. Biomineralization reactions (whether enzymatic or bacterial) are essentially aqueous reactions; water is the reaction medium and the lifeline for bacteria or enzymes to maintain activity. Hydroxypropyl methylcellulose or xanthan gum molecules contain numerous hydrophilic groups (such as hydroxyl and carboxyl groups), which can form strong bonds with water molecules through hydrogen bonds, creating a microscopic hydration protective film. This protective film significantly reduces the free water activity of the solution, inhibiting rapid evaporation of water under high temperatures and strong winds. For biomineralization reactions, this means that the golden window of the reaction system is forcibly extended, ensuring that microorganisms or enzymes do not become inactive due to environmental dryness within the critical few hours after solution spraying, thus guaranteeing the full progress of the calcium carbonate precipitation reaction.
[0060] Aeolian sand has extremely high porosity and permeability. If a low-viscosity pure aqueous solution is used, the cementing solution will rapidly penetrate deeper under gravity, leading to insufficient surface cementation or even loss below the roadbed reinforcement layer. Adding a thickener causes the solution's viscosity to increase exponentially. This high viscosity effectively inhibits the vertical infiltration rate of the solution into the sand's pores, ensuring that more of it remains within the target reinforcement layer or surface crust. This water-locking and sand-fixing effect ensures the enrichment of cementing material within the predetermined depth, avoiding surface pulverization caused by excessive penetration.
[0061] This embodiment, by adding 0.1-0.3% of a water-retaining thickener (such as hydroxypropyl methylcellulose or xanthan gum) to the biomineralization solution, can significantly prolong the effective reaction time, inhibit water evaporation, and ensure that microorganisms or enzymes remain active in arid environments. At the same time, the thickener increases the viscosity of the solution, slows down its penetration rate in sandy soil, effectively enhances the cementing effect of the surface layer, and improves the stability and wind erosion resistance of the protective layer.
[0062] This application provides a desert roadbed obtained by the above-described desert roadbed reinforcement method, comprising: Coarse-grained components, which come into contact with each other to form a load-bearing skeleton; Fine-grained components fill the pores of coarse-grained components; Short-cut geofibers are randomly distributed in three dimensions between the coarse and fine grain components; And calcium carbonate cement; In this process, calcium carbonate cement fills the spaces between the coarse-grained component, the fine-grained component, and the short-cut geofibers, forming a continuous cement network. The surface of the fine-grained component is covered with a calcium carbonate crystal layer, and a calcium carbonate anchoring layer is formed on the surface of the short-cut geofibers. The calcium carbonate crystal layer and the calcium carbonate anchoring layer are interconnected.
[0063] Specifically, in the original state of aeolian sand, the particles are mostly in point contact and lack cohesion. In this embodiment, the coarse-grained component (typically with a particle size greater than 0.075 mm) retained after sieving constitutes the aggregate of the soil. Through close packing, it forms a force transmission chain, bearing the main vertical load and horizontal shear force of the roadbed. The establishment of this skeleton structure ensures the macroscopic stiffness and stability of the roadbed and prevents excessive deformation of the soil under pressure.
[0064] The fine-grained components fill the pores of the coarse-grained components, a structural feature that achieves the dual functions of physical densification and chemical activation. The fine-grained components (particle size <0.075mm) effectively occupy the large pores between the coarse-grained skeleton, significantly reducing the void ratio of the soil and increasing the compaction of the subgrade. This not only reduces the channels for water and air flow but also increases the contact area between particles. More importantly, the selected fine-grained components (such as illite and montmorillonite) have high specific surface area and surface charge activity. During biomineralization, these fine-grained surfaces preferentially adsorb bacterial or enzyme solutions, becoming heterogeneous nucleation sites for calcium carbonate crystal growth. This allows the cementation reaction to occur not only at the contact points of coarse particles but also, through crystal growth on the fine-grained surfaces, to encapsulate and connect the coarse particles, forming a more extensive cementation network.
[0065] Short-cut geofibers are distributed in a three-dimensional random pattern between coarse and fine-grained components, constructing a microscopic reinforcement network. Within the soil, the short-cut geofibers exhibit a spatially random distribution, much like countless tiny anchors interspersed among sand grains. When the subgrade is subjected to external loads causing tensile stress or shear deformation, the short-cut geofibers spanning microcracks are tightened. Stress is transferred through the friction and adhesion between the short-cut geofibers and the soil interface, thereby limiting crack propagation and significantly improving the ductility and tensile strength of the soil.
[0066] Furthermore, during the biomineralization reaction, calcium carbonate crystals not only deposit on the surface of sand grains to form a calcium carbonate crystal layer, but also deposit on the surface of hydrophilic or surface-treated fibers, forming a rough calcium carbonate anchoring layer. This structure enables a seamless connection between the fine-grained crystal layer and the fiber-anchoring layer at the microscopic level. This continuous cementing network integrates the compressive strength of the coarse grains, the filling capacity of the fine grains, and the tensile strength of the fibers into a unified whole. When the subgrade is under stress, stress can be efficiently transferred between the components through the dense calcium carbonate cementing network, avoiding localized damage caused by stress concentration, thus endowing the desert subgrade with extremely high strength, stiffness, and durability.
[0067] This embodiment provides a desert roadbed where coarse-grained components form a load-bearing skeleton, bearing the main vertical loads and horizontal shear forces, ensuring the roadbed's stiffness and stability and preventing excessive deformation. Fine-grained components fill the pores of the coarse-grained components, significantly reducing the void ratio, increasing soil density, reducing water and air circulation channels, and enhancing wind erosion resistance. Short-cut geofibers are distributed in a three-dimensional random pattern, forming a reinforcing network that effectively limits crack propagation under stress, improving tensile strength and ductility. Calcium carbonate cement forms a continuous cementing network between the coarse-grained, fine-grained, and fiber components, with the calcium carbonate crystal layer and calcium carbonate anchoring layer interconnected, enhancing the bonding force of each component and improving overall strength, durability, and compressive strength.
[0068] In one optional embodiment, the fine-grained component is an active clay mineral, and the surface of the fine-grained component is covered with a calcium carbonate crystal layer composed of calcium carbonate crystals with a particle size of 5-20 μm. The calcium carbonate crystals are uniformly distributed in a thin film with the fine-grained component as the nucleation substrate.
[0069] Specifically, reactive clay minerals (such as illite and montmorillonite) have negatively charged surfaces and abundant siloxane groups. In biomineralization solutions, these surface sites are highly reactive for calcium ions (Ca). 2+ It possesses extremely strong electrostatic adsorption capabilities. According to crystal growth theory, the nucleation energy barrier required for crystal formation (calcium carbonate) on a solid surface (clay) is much lower than that for spontaneous nucleation (homogeneous nucleation) in solution. Therefore, activated clay acts as countless micro-seeds, inducing calcium carbonate to preferentially precipitate on its surface rather than randomly precipitating in the porous solution. The particle size range (5-20 μm) is key to achieving dense packing. If the crystals are too large (e.g., >20 μm), large gaps will form between the crystals, resulting in a loose and porous cement layer; if the crystals are too small (e.g., nanoscale), although the specific surface area is large, they are prone to agglomeration and difficult to form a high-strength framework. The 5-20 μm microcrystal size allows for tight stacking on the clay surface, forming a high-density crystal layer, significantly improving the filling efficiency of the cement.
[0070] This embodiment utilizes the negative charge and siloxane groups on the surface of active clay minerals to effectively adsorb calcium ions, promoting the nucleation and growth of calcium carbonate crystals on their surface. The crystal particle size ranges from 5-20 μm, ensuring a high density and uniform distribution of the calcium carbonate crystal layer, thereby significantly improving the filling efficiency and stability of the cementing layer. This uniformly distributed crystal layer enhances the bonding force between fine-grained components and other components, improving the compressive strength, crack resistance, and durability of the subgrade. Furthermore, the dense calcium carbonate crystal layer reduces soil porosity, lowering the pathways for water and air circulation, thus improving the subgrade's resistance to wind erosion and water intrusion. Overall, this technology effectively improves the strength, stability, and durability of the subgrade, exhibiting particularly excellent wind erosion resistance in harsh environments.
[0071] In one alternative embodiment, the desert roadbed has a compaction degree of ≥96%, a calcium carbonate content of 1-2%, an unconfined compressive strength of ≥2.0MPa, a failure strain of ≥2.3%, and a pore coordination number distribution exhibiting a bimodal characteristic dominated by isolated micropores.
[0072] This application provides an application of desert roadbed, in which the desert roadbed obtained by the above-mentioned desert roadbed reinforcement method or the above-mentioned desert roadbed is applied to highway roadbed filling, shoulder reinforcement, slope protection or wind and sand disaster prevention projects in desert areas.
[0073] To better explain and facilitate understanding of this application, a detailed description of its specific embodiments is provided below. Unless otherwise specified in the embodiments, all raw materials used in the embodiments of this application are purchased commercially.
[0074] Example 1 This embodiment studies the effects of the content of short-cut geofibers and the total concentration of calcium ions in the composite calcium source cementitious solution on the reinforcement effect through indoor experiments, in order to determine the optimal material mix ratio.
[0075] The undisturbed aeolian sand used in the experiment was taken from a desert highway in Gansu Province. Its basic characteristics are as follows: uniformity coefficient Cu=3.1, curvature coefficient Cc=1.2, mud content 1.8%, and maximum dry density 1.68 g / cm³. 3 The optimal moisture content is 8.2%. The selected short-cut geotextile fiber is alkali-resistant glass fiber, with a length of 15 mm and a tensile strength ≥1500 MPa. The biological inducing agent is EICP biological solution urease at a concentration of 150 g / L; the composite calcium source cementing solution is a mixture of calcium chloride and urea. The MICP bacterial solution uses Bacillus pasteurii, cultured to the stationary phase with OD600=1.5 and urease activity ≥5 mMurea hydrolyzed / min.
[0076] The experiment investigated two main influencing factors: the content of alkali-resistant glass fiber and the total calcium ion concentration in the composite calcium source binder. The alkali-resistant glass fiber content was set at four levels: 0%, 0.2%, 0.4%, and 0.6% (as a percentage of the total mass of the mixture); the total calcium ion concentration in the composite calcium source binder was set at three levels: 1.0 mol / L, 1.5 mol / L, and 2.0 mol / L. Urea was prepared at a calcium:urea volume ratio of 1:1. A total of 12 mix proportions were designed, with three parallel specimens prepared for each proportion.
[0077] The specimen preparation process is as follows: First, the sieved fine-particle component and the designed amount of alkali-resistant glass fiber are mixed with the sieved coarse-particle component and dry-mixed using a mixer for 3 minutes until uniformly mixed. Then, an equal volume of EICP biological solution and composite calcium source cementitious liquid are mixed and immediately added to the mixture, and stirring is continued for 2 minutes. Next, cylindrical specimens with a diameter of 50 mm and a height of 100 mm are prepared using a servo hydraulic press hydrostatic pressing method, with the loading rate controlled at 1 mm / min and the target dry density at 1.74 g / cm³. 3 (Corresponding to a compaction degree of 96%), the holding time was 2 minutes. After demolding, the specimens were cured at room temperature (25±2℃) for 3 days. Finally, an unconfined compressive strength test was conducted using a universal testing machine at a loading rate of 1 mm / min.
[0078] Experimental results show that when the alkali-resistant glass fiber content is 0.4%, the strength is increased by 160% compared to the fiber-free group, the breaking strain increases by 167%, and the workability is good. When the alkali-resistant glass fiber content is 0.6%, the strength increase is limited (about 5%), but fiber agglomeration increases. When the total calcium ion concentration in the composite calcium source binder is 1.5 mol / L, the strength reaches its peak value at all alkali-resistant glass fiber contents; however, at 2.0 mol / L, the strength decreases slightly. Figure 3 The diagram illustrates the effect of different mix proportions provided in Example 1 on the strength of desert roadbed. According to the test results, the optimal mix proportion is 0.4% alkali-resistant glass fiber content and 1.5 mol / L total calcium ion concentration in the composite calcium source cementitious liquid (corresponding to 1.5 mol / L urea concentration). The 7-day strength can reach 1.35 MPa, and the failure strain is 2.4%.
[0079] Example 2 This embodiment verifies the active nucleation effect of fine-particle components and the synergistic cementation mechanism of the fiber-fine-particle-coarse sand interface through indoor experiments.
[0080] First, the pore volume of the coarse-grained component is calculated. This is based on a maximum dry density of 1.68 g / cm³. 3 Given a soil particle specific gravity of 2.65, the calculated void ratio e = 0.58, corresponding to a pore volume ratio of approximately 36.7%. Taking a standard cylindrical specimen (50 mm diameter, 100 mm height) as an example, its total volume is 196.25 cm³. 3 Therefore, the pore volume is approximately 72.0 cm³. 3 The fine-grained component (particle size < 0.075 mm) used was obtained by sieving undisturbed aeolian sand.
[0081] Four groups of fine particle content were set up for the experiment: a control group (no fine particles), and groups with fine particle volume accounting for 33.3%, 66.7%, and 100% of the pore volume of the coarse particle component, respectively. All specimens were prepared using the optimal mix proportion determined in Example 1 (fiber content 0.4%, calcium ion concentration 1.5 mol / L) and treated using EICP and MICP processes, respectively. The specimens were statically pressed using a servo hydraulic press with a compaction load of 10 MPa and a holding time of 2 min. After curing for 7 days, unconfined compressive strength tests were conducted.
[0082] The experimental results showed that the variation patterns of the EICP group and the MICP group were basically the same: the 7-day strength of the control group without fine particles was 1.35 MPa (EICP) and 1.38 MPa (MICP), respectively; when the volume of fine particles accounted for 66.7% of the pore volume, the strength reached 1.40 MPa (EICP) and 1.43 MPa (MICP), respectively, which were 3.7% and 3.6% higher than the control group.
[0083] To further verify the active nucleation effect of fine particles, a comparative experiment was set up: purchased quartz sand was used to replace the in-situ fine particles. Under the same dosage (accounting for 66.7% of the pore volume), the 7-day strength of the EICP group was 1.22 MPa, which was 13.4% lower than that of the in-situ fine particle group. This indicates that the active surface of the in-situ fine particles is an important factor in improving the mineralization efficiency.
[0084] Please see Figure 4 Scanning electron microscopy (SEM) observations revealed that in the control group, calcium carbonate mainly existed as large-sized (>10 μm) calcite aggregates, randomly distributed at particle contact points. In contrast, in the fine-particle-doped group, the fine-particle surface was uniformly coated with a nano-scale calcium carbonate film, forming a rough calcium carbonate anchoring layer on the fiber surface. At the fiber-fine-particle-coarse sand interface, calcium carbonate crystals constituted continuous gradient cementation bridges, thus achieving a synergistic reinforcement effect at the three-phase interface. It should be noted that in the figure, Ca on the horizontal axis represents calcium ion concentration, F represents fiber doping, and EICP / MICP indicates the treatment method.
[0085] Example 3 This embodiment studies the effect of compaction load on reinforcement through indoor experiments and verifies the spatial confinement effect of vibration compaction on calcium carbonate crystals.
[0086] First, please refer to Figure 5(a), which is a schematic diagram showing the effect of different compaction loads on the dry density of the specimen provided in Example 3. Figure 5(b) is a schematic diagram showing the effect of different compaction loads on the unconfined compressive strength (UCS) of the specimen provided in Example 3. Figure 5(c) is a schematic diagram showing the effect of different compaction loads on the degree of compaction of the specimen provided in Example 3. Three different levels of compaction loads were set: 5 MPa, 10 MPa, and 15 MPa. The test results show that when the compaction load is 5 MPa, the dry density is 1.61 g / cm³. 3 (Compaction degree 92.5%), the 7-day strength of the EICP group is 0.86 MPa; when the compaction load is 10 MPa, the dry density is 1.73 g / cm³. 3 (Compaction degree 96.0%), EICP group strength is 1.35 MPa; when the compaction load is 15 MPa, the dry density is 1.77 g / cm³. 3 (Compaction degree 98.3%), the EICP group strength was 1.58 MPa. As the compaction degree increased from 92.5% to 96.0%, the specimen strength increased by 55%–57%. This indicates that increasing compaction energy can effectively overcome the frictional resistance between particles, making the aeolian sand skeleton more compact and providing a dense physical space for subsequent biomineralization reactions; high compaction not only reduces porosity but also promotes the effective cementation of calcium carbonate crystals at particle contact points, thereby significantly improving the bearing capacity of the subgrade.
[0087] Please see Figure 6 The stress-strain curves for different compaction loads and fine-grained component contents provided in Example 3 are shown. It can be seen that the specimen under a 15 MPa compaction load has the highest peak stress, reaching approximately 1.58 MPa; while the 10 MPa group, although slightly weaker in strength, exhibits good ductility. Furthermore, comparing the curves of the control group with 0% and 33.3% fine-grained components shows that an appropriate amount of fine-grained component can significantly increase the slope of the rising segment of the curve, i.e., increase the modulus of the soil.
[0088] To further verify the spatial constraint effect of vibration compaction on crystal growth, a comparative experiment was conducted in this embodiment between static pressing and vibration molding. The results showed that in the statically pressed specimens, calcium carbonate crystals formed large (>10 μm) calcite aggregates with uneven distribution; while in the vibration-molded specimens, the vibration energy constrained the crystallization space of the calcium carbonate crystals, causing the crystals to grow in a restricted manner within micron-sized pores, ultimately forming a uniform cemented film with a particle size of 5-20 μm.
[0089] Please see Figure 7Through X-CT three-dimensional reconstruction and pore network model (PNM) analysis, the total porosity of the vibration-molded specimen was reduced to 0.92%, and the pore coordination number distribution exhibited a bimodal characteristic. Macropores were divided into isolated micropores by the fine-grained calcium carbonate complex, and the seepage channels were effectively cut off, thereby improving the specimen's impermeability.
[0090] Example 4 To verify the field applicability of the desert roadbed and construction technology of this invention, a 50m test section was selected at a sandy soil construction site for process verification. The soil in the test section was typical local sandy soil, and its main physical properties were highly similar to those of desert aeolian sand: uniformity coefficient (Cu=2.8), curvature coefficient (Cc=1.1), mud content 2.1%, and maximum dry density 1.69g / cm³. 3 The optimal moisture content is 8.5%.
[0091] The construction adopted the optimal mix ratio selected indoors: fiber content 0.4% (alkali-resistant glass fiber, length 15mm), calcium ion concentration 1.5mol / L, urea concentration 1.5mol / L, and urease solution concentration 150g / L. The roadbed treatment width is 1m, the treatment depth is 0.5m, and it is constructed in 2 layers, with each layer compacted to a thickness of 25cm.
[0092] The construction process is as follows: After the base is leveled, alkali-resistant glass fiber is evenly spread on the surface of sandy soil and mixed to a depth of 20-25cm using a road mixer, with at least two mixing passes. EICP biological solution and composite calcium source cementitious liquid were stored separately and mixed online at a 1:1 ratio using a static mixer before spraying. The mixture was then evenly sprayed onto the surface of the fiber-soil mixture using an intelligent spraying vehicle at a rate of 3.0 L / m². 2 ; Within 20 minutes after spraying, compaction is carried out using a vibratory roller (excitation force 320kN, vibration frequency 30Hz). The compaction process consists of one pass of static compaction, two to three passes of vibratory compaction, and one pass of static compaction. After repeated layering and construction up to the design elevation, spray the surface with 1.5 L / m² of EICP biological solution. 2 Cover with geotextile and keep moist for 24 hours to form a sealing layer.
[0093] Unit samples were poured on-site at representative locations within the test section and, after standard curing, were subjected to indoor testing. Results showed that the average on-site compaction degree was 97.2%, and the average dry density was 1.74 g / cm³. 3 The average unconfined compressive strength over 7 days was 1.38 MPa, the average failure strain was 2.3%, and the average resilient modulus was 112 MPa, all of which meet the design requirements.
[0094] Please refer to Figure 8(a), which shows the effect of different mix proportions provided in Example 4 on ultrasonic velocity and calcium carbonate content. With the optimization of cementitious liquid concentration (e.g., C2P10E12.2 group), the ultrasonic velocity significantly increases, reaching a maximum of 3.0 km / s, indicating the formation of a continuous and dense cemented structure within the soil. Simultaneously, the trend of calcium carbonate content change shown by the red line is consistent with the strength growth trend, verifying that the amount of calcium carbonate precipitation is a key factor determining strength. Figure 8(b) shows the effect of different mix proportions provided in Example 4 on resistivity. With the progress of biomineralization reaction, the resistivity of the specimen shows an upward trend. This is because the generated calcium carbonate crystals (shown by the gray line) fill the pores, cutting off the conductive channels of pore water. The maximum increase in resistivity corresponds to the peak value of calcium carbonate content, further confirming the reinforcement mechanism of pore filling-cementation enhancement.
[0095] Compared with the traditional gravel soil replacement scheme used in adjacent sections, the construction period and cost of this invention are significantly reduced, verifying the on-site applicability of desert roadbed and construction technology.
[0096] In summary, by innovatively utilizing the original aeolian sand along the desert highway and actively separating and utilizing its natural fine-grained components, local material sourcing is achieved, eliminating the need for long-distance transportation and replacement. This significantly reduces material costs by 60% to 80%, and only one biomineralization treatment is required to achieve an unconfined compressive strength of 2.0 MPa. Compared to traditional methods that require 3 to 4 cycles of reinforcement, this method significantly improves efficiency, increases construction efficiency by more than 50%, and greatly shortens the construction period. Its core lies in achieving synergistic reinforcement of the interface between fibers, fine particles, and coarse sand during the calcium carbonate crystallization process: fine particles, as the preferential nucleation substrate, preferentially adsorb biological inducing agents and induce calcium carbonate to grow heterogeneously on their surface into a uniform cemented film; coarse particles, as the load-bearing skeleton, are wrapped by a calcium carbonate film on their surface, forming a continuous interface transition with the fine particle cemented film; fibers, as a three-dimensional anchoring network, form a rough cemented layer on their surface, interpenetrating and overlapping with the fine particle-calcium carbonate composite; at the interface of the three, calcium carbonate crystals form a continuous gradient cemented bridge, achieving synergistic reinforcement of "fine particle nucleation - coarse sand load-fiber anchoring", transforming the "point-to-point" stress concentration mode between particles in traditional biomineralization reinforcement into a "surface force" uniform force transmission mode, fundamentally changing the force chain transmission mechanism, and significantly improving the bearing capacity, ductility, and fatigue resistance of the roadbed. At the same calcium carbonate (CCC) content, the unconfined compressive strength (UCS) of soil treated using this method can be increased by an order of magnitude compared to the traditional method. Experimental data show that when the calcium carbonate content is only 1%, the UCS can reach 2 MPa, and the failure strain is ≥2.3%, which is more than double that of the traditional method. X-CT three-dimensional reconstruction and pore network model (PNM) analysis show that the total porosity of the soil treated using this method can be reduced to 0.92%, and the pore coordination number distribution exhibits a bimodal characteristic. Large pores are divided into isolated micropores by fine-grained calcium carbonate complexes, and the seepage channels are effectively cut off. Ultrasonic pulse velocity (UPV) tests show that the UPV of the treated soil can be increased from 0.16 km / s to 3.00 km / s, and the maximum decrease in resistivity reaches 109.01%, proving the formation of a dense and continuous structure. Furthermore, this solution utilizes conventional highway construction machinery (screening equipment, road mixing machines, vibratory rollers, and spray trucks), requiring no specialized equipment. It is suitable for various scenarios such as new roadbed construction, widening of existing roads, and slope protection. Furthermore, it employs bio-enzymes and natural fibers, resulting in no environmental pollution and promoting ecological restoration of highway slopes. The surface sealing layer effectively resists wind erosion, providing a stable foundation for vegetation growth. It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover a non-exclusive inclusion, such that a process, method, product, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, product, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, product, or apparatus that includes said element.
[0097] The above description is merely an embodiment of this application and is not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.
[0098] Although embodiments of this application have been described in conjunction with the accompanying drawings, those skilled in the art can make various modifications and variations without departing from the spirit and scope of this application, and such modifications and variations all fall within the scope defined by the appended claims.
Claims
1. A method for reinforcing desert roadbeds, characterized in that, The reinforcement method includes: The original aeolian sand along the desert highway is screened to separate fine particles with a particle size less than 0.075 mm and coarse particles with a particle size greater than or equal to 0.075 mm. The screened fine particles are then premixed with short-cut geotextiles to form a fiber-fine sand mixture. The fiber-fine sand mixture is then mixed with the screened coarse particles to obtain a mixture. The biomineralization solution obtained by mixing the bio-inducing agent with the composite calcium source cementing solution is sprayed into the mixture and stirred to obtain the mixed material; The mixture is vibrated and compacted within a preset time to form a roadbed reinforcement layer; Repeat the above steps of preparing the mixture, preparing the mix, and vibrating compaction layer by layer according to the preset thickness to fill the desert roadbed to be reinforced in layers. After filling to the design elevation, spray the biomineralization solution on the road shoulders and slopes and maintain them to form a reinforced desert roadbed. The mineral components in the fine-grained component include one or more of illite and montmorillonite; The biological inducer includes EICP biological solution or MICP bacterial solution; The total calcium ion concentration in the composite calcium source cementing solution is 1.5-2.0 mol / L, and the urea concentration is 1.5-2.0 mol / L.
2. The reinforcement method according to claim 1, characterized in that, The fine-grained component is added at a rate of 50-80% of the pore volume of the coarse-grained component; The chopped geofiber is selected from one or more of alkali-resistant glass fiber, polypropylene fiber, or polyacryl alcohol fiber. The chopped geofibers are 12-18 mm in length and are added at a rate of 0.3-0.6% of the total mass of the mixture.
3. The reinforcement method according to claim 1, characterized in that, The biomineralization solution obtained by mixing the bio-inducing agent with the composite calcium source cementing solution is sprayed into the mixture and stirred to prepare the mixture, comprising: The biological inducer and the composite calcium source cementing solution are mixed at a volume ratio of 1:1 to obtain a biomineralization solution.
4. The reinforcement method according to claim 1, characterized in that, The vibration compaction includes: Perform static compaction once using a vibratory roller, followed by 2-3 vibratory compaction passes until the compaction degree reaches over 96%.
5. The reinforcement method according to claim 1, characterized in that, The preset thickness is 20-30cm.
6. The reinforcement method according to claim 1, characterized in that, The spraying rate of the biomineralization solution for the road shoulders and slopes is 1.5-2.0 L / m². 2 The maintenance mentioned refers to covering the geotextile and maintaining moisture for at least 48 hours.
7. The reinforcement method according to claim 1, characterized in that, The biomineralization solution contains 0.1-0.3% by mass of a water-retaining thickener, wherein the water-retaining thickener is hydroxypropyl methylcellulose or xanthan gum.
8. The desert roadbed obtained by the desert roadbed reinforcement method according to any one of claims 1-7, characterized in that, include: Coarse-grained components, which come into contact with each other to form a load-bearing skeleton; Fine-grained components fill the pores of the coarse-grained components; Short-cut geofibers are three-dimensionally randomly distributed between the coarse-grained component and the fine-grained component; And calcium carbonate cement; The calcium carbonate cement fills the space between the coarse-grained component, the fine-grained component, and the short-cut geofibers, forming a continuous cement network. The surface of the fine-grained component is covered with a calcium carbonate crystal layer, and a calcium carbonate anchoring layer is formed on the surface of the short-cut geofibers. The calcium carbonate crystal layer and the calcium carbonate anchoring layer are interconnected.
9. The desert roadbed according to claim 8, characterized in that, The fine-grained component is an active clay mineral, and the surface of the fine-grained component is covered with a calcium carbonate crystal layer composed of calcium carbonate crystals with a particle size of 5-20 μm. The calcium carbonate crystals are uniformly distributed in a thin film with the fine-grained component as the nucleation substrate.
10. The desert roadbed according to claim 8, characterized in that, The desert roadbed has a compaction degree of ≥96%, a calcium carbonate content of 1-2%, an unconfined compressive strength of ≥2.0MPa, a failure strain of ≥2.3%, and a pore coordination number distribution exhibiting a bimodal characteristic dominated by isolated micropores.
Citation Information
Patent Citations
Recycling method of dust removal filter bag in coal-fired power plant
CN107746222A
Basalt fiber reinforced aeolian sand based on MICP technology and preparation method thereof
CN116081983A